2022
DOI: 10.1155/2022/3642349
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of XinJiaCongRongTuSiZiWan on the Reproductive Toxicity of Female Rats Induced by Triptolide

Abstract: Background. Although triptolide (TP) has been widely used for the treatment of inflammatory, autoimmune diseases, and various kinds of tumors, the long experimental and clinical applications have exhibited severe reproductive system toxicity in TP-treated animals and patients. More importantly, the underlying molecular mechanism involved in TP-induced reproductive system toxicity still needs more research. Methods. Adult female Sprague Dawley rats and human ovarian granulosa cell lines were treated with TP and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…The total amount of crude drug for each dose of XJCRTSZW is 120 g, which was made by the Department of Pharmacy of Chengdu University of Traditional Chinese Medicine. The methods were consistent with previous reported 12 . The concentrations of XJCRTSZW in the high, middle, and low groups, as well as EV and medroxyprogesterone acetate, were determined using an adult clinical dose of 6 kg per kilogram of body weight and a human to rat conversion ratio of 1:20.…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…The total amount of crude drug for each dose of XJCRTSZW is 120 g, which was made by the Department of Pharmacy of Chengdu University of Traditional Chinese Medicine. The methods were consistent with previous reported 12 . The concentrations of XJCRTSZW in the high, middle, and low groups, as well as EV and medroxyprogesterone acetate, were determined using an adult clinical dose of 6 kg per kilogram of body weight and a human to rat conversion ratio of 1:20.…”
Section: Methodssupporting
confidence: 92%
“…Our group has discovered an effective treatment of XJCRTSZW on POF and PCOS 11 , 12 . Furthermore, our previous results have also shown that XJCRTSZW reduces the TP-induced enhancement of apoptosis and macroautophagy.…”
Section: Introductionmentioning
confidence: 99%
“…Toxic side effects of T. wilfordii have also been reported for the reproductive system, as exemplified by instances of amenorrhea in women and reduced sperm counts in men (Singla and Challana, 2014), and these have been found to be significantly correlated with patient age, drug dosage, and course of treatment. As a cytotoxic medication, T. wilfordii mainly acts on follicular cells, thereby reducing the level of estrogen secreted by these follicles (Deng et al, 2022). Additionally, preparations of this plant can reduce progesterone levels, thereby altering the levels of hormones in the hypothalamus-pituitary-gonadal axis and leading to abnormalities in the menstrual cycle and thus menstrual disorders or amenorrhea.…”
Section: Reproductive Toxicitymentioning
confidence: 99%